Migration-Related Conflicts as Drivers of Institutional Change? - Maria Budnik; Katrin Grossmann; Christoph Hedtke (Urban Planning, 2021)
This article examines the role of social conflicts in the context of migration and discusses the relation between such conflicts and institutional change. We understand conflicts as tensions that evoke contradiction between different social groups or institutional actors. Varied urban contexts together with dynamic immigration of heterogeneous population groups can induce negotiation processes that affect institutional settings and actors. Conflicts have therefore been an integral part of urban coexistence, and cities have always been places where these conflicts play out. We assume that conflicts are social phenomena, which have multiple causes and effects. Public assumptions about conflicts in connection with migration often have a negative or destructive impetus, while conflict theory ascribes to conflicts potential positive effects on societal change. Conflicts can represent forms of socialization and the possibility of adapting or changing social conditions. This article discusses the extent to which migration-related conflicts induce institutional change. Using qualitative empirical results from the BMBF-funded research project MigraChance, we present a case study that reconstructs the emergence and course of a conflict surrounding the construction of a Syriac-Orthodox church in Bebra (Hesse) in the 1990s. Analyzing this conflict both in depth and in relation to its local context, we show that migration is only one part of what we refer to as migration-related conflicts, and we shed light on the complexity of factors that can result in institutional change. Change can also occur indirectly, in small steps, and with ambivalent normative implications.